Do macrophages play a role in the adverse effects of endocrine disrupting chemicals (EDCs) on testicular functions? - Cui, Haoyi; Culty, Martine (Frontiers in Toxicology, 2023)
During the past decades, several endocrine disrupting chemicals (EDCs) have been confirmed to affect male reproductive function and fertility in animal studies. EDCs are suspected to exert similar effects in humans, based on strong associations between levels of antiandrogenic EDCs in pregnant women and adverse reproductive effects in infants. Testicular macrophages (tMΦ) play a vital role in modulating immunological privilege and maintaining normal testicular homeostasis as well as fetal development. Although tMΦ were not historically studied in the context of endocrine disruption, they have emerged as potential targets to consider due to their critical role in regulating cells such as spermatogonial stem cells (SSCs) and Leydig cells. Few studies have examined the impact of EDCs on the ability of testicular cells to communicate and regulate each other’s functions. In this review, we recapitulate what is known about tMΦ functions and interactions with other cell types in the testis that support spermatogenesis and steroidogenesis. We also surveyed the literature for reports on the effects of the EDCs genistein and DEHP on tMΦ, SSCs, Sertoli and Leydig cells. Our goal is to explore the possibility that EDC disruption of tMΦ interactions with other cell types may play a role in their adverse effects on testicular developmental programming and functions. This approach will highlight gaps of knowledge, which, once resolved, should improve the risk assessment of EDC exposure and the development of safeguards to protect male reproductive functions.